1985
DOI: 10.1007/bf00219250
|View full text |Cite
|
Sign up to set email alerts
|

Retinal projections in the caecilian Ichthyophis kohtaoensis (Amphibia, Gymnophiona)

Abstract: The retinal projections of the caecilian Ichthyophis kohtaoensis were investigated by anterograde transport of HRP. The optic tract forms two bundles in the diencephalon, a narrow medial bundle in the optic tectum, and a basal optic tract consisting of few fibres. Terminal fields are in the thalamus, pretectum, tectum, and as a circumscribed basal optic neuropile in the tegmentum. Thalamic, pretectal and tectal projections are contralateral as well as ipsilateral. The reduced but existing visual projection cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 7 publications
4
48
1
Order By: Relevance
“…Except for the telencephalic projections, all retinal recipient areas were bilateral, but projections were heavier contralaterally in most target areas. The results coincide basically with those in Acipenser gülden-städti [Repérant et al, 1982], Polypterus palmas, Lepisosteus osseus [Braford and Northcutt, 1983], Lepisosteus platyrhincus [Collin and Northcutt, 1995], Amia calva [Butler and Northcutt, 1992], and Platyrhinoidis triseriata [Northcutt and Wathey, 1980], Lamperta fluviatilis [Vesselkin et al, 1980], Eptatretus burgeri [Kusunoki and Amemiya, 1983], Eptatretus stouti [Wicht and Northcutt, 1990], European Salamandridae [Salamandra salamandra, Triturus cristatus and Triturus alpestris ;Fritzsch, 1980], Ichthyophis kohtaoensis [Himstedt and Manteuffel, 1985], and Bufo marinus [Wye-Dvorak et al, 1992] in that a part of the optic nerve does not decussate at the chiasm, and reaches the ipsilateral target areas. However, Braford and Northcutt [1983] reported that projections to the accessory optic nucleus in Polypterus palmas and Lepisosteus osseus, and to the ventrolateral thalamic nucleus and superficial pretectal nucleus in Lepisosteus osseus are only contralateral.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Except for the telencephalic projections, all retinal recipient areas were bilateral, but projections were heavier contralaterally in most target areas. The results coincide basically with those in Acipenser gülden-städti [Repérant et al, 1982], Polypterus palmas, Lepisosteus osseus [Braford and Northcutt, 1983], Lepisosteus platyrhincus [Collin and Northcutt, 1995], Amia calva [Butler and Northcutt, 1992], and Platyrhinoidis triseriata [Northcutt and Wathey, 1980], Lamperta fluviatilis [Vesselkin et al, 1980], Eptatretus burgeri [Kusunoki and Amemiya, 1983], Eptatretus stouti [Wicht and Northcutt, 1990], European Salamandridae [Salamandra salamandra, Triturus cristatus and Triturus alpestris ;Fritzsch, 1980], Ichthyophis kohtaoensis [Himstedt and Manteuffel, 1985], and Bufo marinus [Wye-Dvorak et al, 1992] in that a part of the optic nerve does not decussate at the chiasm, and reaches the ipsilateral target areas. However, Braford and Northcutt [1983] reported that projections to the accessory optic nucleus in Polypterus palmas and Lepisosteus osseus, and to the ventrolateral thalamic nucleus and superficial pretectal nucleus in Lepisosteus osseus are only contralateral.…”
Section: Discussionsupporting
confidence: 64%
“…We also compare the present data with those obtained in four species of chondrichthyans [Nagaprion brevirostris, Graeber and Ebbesson, 1972;Ginglymostoma cirratum, Luiten, 1981a, b; Rhinobatos productus, Ebbesson and Meyer, 1980; Platyrhinoidis triseriata, Northcutt and Wathey, 1980] as well as several teleost species [e.g. Vanegas and Northcutt and Wullimann, 1988;Butler and Saidel, 1991;Ito et al, 1992], lampreys [Vesselkin et al, 1980[Vesselkin et al, , 1984, hagfishes [Kusunoki and Amemiya, 1983;Wicht and Northcutt, 1990], lungfishes [Northcutt, 1977], and amphibians [Fritzsch, 1980;Fritzsch and Himstedt, 1981;Himstedt and Manteuffel, 1985;Uchiyama, 1989;Wye-Dvorak et al, 1992].…”
Section: Discussionmentioning
confidence: 85%
“…The first one refers to the rich nitrergic innervation of the retinocipient neuropils in the ventral thalamus. Tracing studies are very scarce in gymnophionans, but the identification of the thalamic neuropil in the region with dense nitrergic innervation has been experimentally confirmed [Himstedt and Manteuffel, 1985]. The second was observed in the pretectal region where nitrergic cell groups were present in all species studied.…”
Section: Diencephalonmentioning
confidence: 94%
“…However, if the situation in Dermophis is similar to that of Ichthyophis [Himstedt and Manteuffel, 1985] the retinal axons in the tectum would be restricted to the medial and superficial zone and, therefore, an overlap with the nitrergic fibers might occur. This evidence is in line with the previously mentioned nitrergic innervation of retinocipient regions in the diencephalon of Dermophis.…”
Section: Mesencephalonmentioning
confidence: 99%
“…During prey capture, the forelimbs are extended and used to capture prey and move it to the mouth. In a third amphibian group, the limbless caecilian Ichthyophis kohtaoensis displays contralateral retinal projections as well as IRP [Himstedt and Manteuffel, 1985].…”
Section: Vp: In the Agamid Uromastix Acanthinurusmentioning
confidence: 99%